The effect of wind force on metal deck roof joint - Marshiela, Maedika (2014)
Wind related damage had been rapidly increase in Malaysia. Previous record most of the failure occurred at roof structure system. Roof metal decking is commonly used now in roof structure system in Malaysia. Pull through failure mostly occurred due to insufficient connection. Therefore this study is conducted to investigate the potential of failure and to provide the information related to connection in roof metal decking system. From previous study it was been identify that the maximum failures load of screw connection is 0.99 kN A general metal roof deck used in Malaysia were identified and been analysed. Two different connection type were used which is screw and nail in this study. The spacing between the connection been model are 300 mm, 600 mm, 900 mm and 1200 mm. Finite Element software were used to analyse the force acting to the connection. From the result it was shown that the maximum spacing of screw connection to resist wind speed at 32.5 m/s is 1100 mm. Result also shown that by increasing the spacing distance of connection will affect the risk to failure. It can be concludes that the spacing of the connection are very important in order to resist wind storm.